Infection of bovine T cell clones with genotypically distinct Theileria parva parasites and analysis of their cell surface phenotype - Conrad, P.A.; Baldwin, Cynthia L.; Brown, W.C.; Sohanpal, B.K.; Dolan, T.T.; Goddeeris, Bruno M.; Demartini, J.C.; Ole-MoiYoi, O.K. (Cambridge University Press, 1989)
Different stocks and stabilates within a stock ofTheileriaparvawere analysed for genotypic differences and for their effect on the expression of host cell surface antigens following infection of BoT8+T lymphocyte clones. The parasites were characterizedin vitroby hybridization ofT. parva- specific DNA probes to Southern blots of endonuclease-digested DNA from the infected T cell clones. Phenotypic changes in the host lymphoblastoid cells before and after infection were examined using lineage-specific monoclonal antibodies which reacted with the differentiation antigens BoT2, BoT4, Bo6, BoT8 and a null cell marker on bovine T cells. Expression of Class I and Class II major histocompatibility complex (MHC) antigens on the cell populations was also assessed. Results of this study indicate that genotypically different parasites exist among and withinT. parvastabilates and that the expression of Bo6, BoT8 and the null cell marker was differentially altered by infection with parasites from different stocks or from different stabilates of the same stock. Expression of Class II antigens was significantly increased after infection. Moreover, clones that were derived from the same cell line but had genotypically distinctT. parvaparasites, also showed differences in expression of Bo6 and BoT8 and the null cell marker.